The Effect of Differentiated Learning Approaches on Student Engagement and Self-Confidence in Social Studies Instruction among Elementary Teacher Education Students at Universitas Pahlawan Tuanku Tambusai (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to examine the effect of differentiated learning on the learning engagement and self-confidence of students enrolled in the Elementary Teacher Education Program (PGSD). Specifically, the study focuses on how differentiated instruction facilitates active participation, supports the development of interpersonal skills, and enhances the professional competencies of pre-service teachers. Research Method: This study employed a quasi-experimental design using a Pretest–Posttest Control Group Design. The sample consisted of 60 PGSD students, who were divided into an experimental group receiving differentiated learning instruction and a control group receiving conventional instruction. Data were collected through questionnaires measuring learning engagement and self-confidence. The data were analyzed using independent samples t-tests and Multivariate Analysis of Variance (MANOVA) to determine the effect of the instructional treatment on both dependent variables. Research Findings: The results indicate that the experimental group demonstrated a statistically significant improvement in both learning engagement and self-confidence compared to the control group. Learning engagement showed a substantial increase from pretest to posttest scores, as did self-confidence. These findings confirm the effectiveness of differentiated learning strategies in fostering student involvement, active participation, and confidence within the learning process. Novelty: This study highlights that differentiated learning is effective in higher education, particularly in Elementary Teacher Education programs. The findings show that differentiated instruction enhances social analysis skills, including identifying classroom diversity, analyzing student interactions, and proposing pedagogical solutions, while also fostering creativity and critical thinking to support the professional competence of pre-service teachers.